ASTD 2004 competency study mapping the future : new workplace learning and performance competencies (American Society for Training & Development, 2004)
This powerful new competency model provides a strategic roadmap for today's workplace learning and performance (WLP) professional. By clearly identifying current and emerging trends and competencies, ASTD Competency Study: Mapping the Future is a key resource for a diverse group of individuals, including those who are just entering the field, those who are making hiring decisions, or creating curricula, and individuals looking for career development guidance and ways to bring greater value to their organizations. Developed through an extensive review and validation process, this competency study represents the focused effort of more than 100 WLP experts and bases its conclusions on survey data from more than 2,000 WLP professionals. Despite its solid research base, this is a highly readable book with practical applications and tools that can be put to use immediately by its readers.